2022
DOI: 10.3390/electronics11010156
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Networks and Deep Learning Techniques Applied to Radar Target Detection: A Review

Abstract: Radar target detection (RTD) is a fundamental but important process of the radar system, which is designed to differentiate and measure targets from a complex background. Deep learning methods have gained great attention currently and have turned out to be feasible solutions in radar signal processing. Compared with the conventional RTD methods, deep learning-based methods can extract features automatically and yield more accurate results. Applying deep learning to RTD is considered as a novel concept. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 108 publications
0
18
0
Order By: Relevance
“…The authors in Ref. [4] described a review of the applications of deep learning in the field of radar target detection and summarised the possible limitations. The results obtained in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in Ref. [4] described a review of the applications of deep learning in the field of radar target detection and summarised the possible limitations. The results obtained in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in Ref. [4] have shown that deep learning-based detectors perform better than traditional processing methods to a certain degree in some specific cases. The study of deep learning in the field of radar target detection is at the initial stage and still faces some challenges.…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on the quality of the bounding boxes in annotated dataset for 2D object detection using camera data. Moreover the considerations and conclusions drawn in this paper can be easily expanded to 2D and 3D object detection based on different sensors, such as LiDAR [8] and RADAR [9]. To understand the importance of labels, one can imagine to work on a image classification task with vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach for detection can be established via implementation of the algorithms based on artificial neural networks (ANN) in radar-processing units. Such algorithms as shown in [32,33] may potentially provide a higher level of overall performance. However, they require a training step to be properly conducted.…”
Section: Introductionmentioning
confidence: 99%